Feeding environments of New Zealand - Williams, Murray; Holdaway, Richard N; Rogers, Karyne M (Wildfowl, 2012)
The likely feeding environments of individuals from each of the three populations of New Zealand’s extinct merganser Mergus australis were interpreted from stable isotope ratios of carbon (13C/12C) and nitrogen (15N/14N) in fossil bones and tissue from preserved skins. Analyses of feather and claws from 10 specimens from Auckland Islands indicated the birds fed predominantly on marine prey but that some freshwater-sourced foods may also have been consumed. Stable isotope values from three bones of mergansers from Chatham Island strongly suggest a marine feeding habit while those from two mainland New Zealand bones indicated the birds fed mostly in fresh water. Merganser bones found at a New Zealand lake (Poukawa) suggest this species occupied mainland New Zealand’s fresh waters at the time of first human settlement.